2003
DOI: 10.1038/sj.bmt.1703905
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of an automated closed fluid management device: CytomateTM, for washing out DMSO from hematopoietic stem cell grafts after thawing

Abstract: Summary:Infusion of dimethylsulfoxide (DMSO) contained in cryopreserved and thawed hematopoietic stem cell (HSC) grafts is frequently associated with mild or moderate adverse reactions, and occasionally with more severe events including neurological symptoms. The severity of these complications is related to the amount of residual DMSO. We evaluated a recently available, closed, automated and 'cgmp (current good manufacturing practice) compliant' device (CytoMate TM ) for its ability to wash out DMSO at the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 21 publications
4
68
0
Order By: Relevance
“…Reported adverse reactions to DMSO include nausea and vomiting, abdominal cramps, chills, dyspnea, hypotension or hypertension, bradycardia, arrythmias, alveolar hemorrhage, acute renal failure, and cardiac or respiratory arrest (Alessandrino et al, 1999;Calmels et al, 2003;Hoyt, Szer, & Grigg, 2000;Windrum et al). Aside from toxic reactions to DMSO, acute hemolytic reactions caused by donor-recipient major ABO incompatibility and febrile non-hemolytic reactions may occur.…”
Section: During Stem Cell Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported adverse reactions to DMSO include nausea and vomiting, abdominal cramps, chills, dyspnea, hypotension or hypertension, bradycardia, arrythmias, alveolar hemorrhage, acute renal failure, and cardiac or respiratory arrest (Alessandrino et al, 1999;Calmels et al, 2003;Hoyt, Szer, & Grigg, 2000;Windrum et al). Aside from toxic reactions to DMSO, acute hemolytic reactions caused by donor-recipient major ABO incompatibility and febrile non-hemolytic reactions may occur.…”
Section: During Stem Cell Transplantationmentioning
confidence: 99%
“…The concentrated stem cells then are diluted with an equal volume of human serum albumin solution supplemented with a cryopreservative. Cryopreservation techniques allow for optimal preservation of hematopoietic function and viability of cells (Calmels et al, 2003) Prior to storage, 10% dimethyl sulfoxide (DMSO) is added to the stem cells as a cryoprotectant. DMSO stabilizes cell membranes under rapidly changing conditions and prevents intracellular ice crystal formation during freezing and heat release throughout the period of phase transition, preserving stem cell integrity (Calmels et al;Windrum, Morris, Drake, Niederwieser, & Ruutu, 2005).…”
Section: Stem Cell Processing and Cryopreservationmentioning
confidence: 99%
“…Lemarie and colleagues used comprehensive automated washing to reach more than 20-fold reduction of DMSO-levels, whereas Syme and coworkers investigated patients with solid tumors and used a relatively extensive manual DMSO depletion (Lemarie et al, 2005;Syme et al, 2004). In the preclinical studies mentioned above (Calmels et al, 2003;Rodriguez et al, 2005), the researhers used a device; CytoMate TM , to perform the washing procedure with phosphate buffered saline (PBS) plus 5% Dextran-40, 5% ACD-A and 1-5% human serum albumin (HSA). While Calmels et al achieved more than 96% elimination of DMSO and a mean recovery of viable total cells, CD34+ cells and lymphocyte subsets above 60%, Rodriguez et al reported 98% DMSO elimination and 103% CD34+ cell recovery.…”
Section: Washing Autografts To Remove Dmsomentioning
confidence: 99%
“…Some of the studies where DMSO depletion was utilized, included a large group of patients without bone marrow disease and may not be representative for the present use of autologous peripheral blood stem cell transplantation for hematological malignancies with diffuse infiltration of malignant cells throughout the bone marrow (Calmels et al, 2003;Rodriguez et al, 2005). These preclinical studies investigated grafts of highly selected patients who relapsed or died before autotransplantation could be done (Calmels et al, 2003;Rodriguez et al, 2005). Furthermore, Foïs et al cryopreserved autografts with voluven + DMSO 10% and not DMSO alone, and they did not include detailed analyses of engraftment and transfusion.…”
Section: Washing Autografts To Remove Dmsomentioning
confidence: 99%
“…Therefore, fast and accurate assessment of the CPA concentration in the cell suspension during addition and removal is very important. In order to assess the CPA concentration in cell suspensions, a few methods have been applied by researchers, such as capillary zone electrophoresis [7]), high-performance liquid chromatography (HPLC) [8], and gas chromatography [9]. However, all these approaches are very complex, time-consuming, and expensive.…”
Section: Introductionmentioning
confidence: 99%